O que se sabe sobre a dieta de Chrysocyon Brachyurus (Carnivora: Canidae) no Brasil? - Soares, Arthur Celestino (2020)
Chrysocyon brachyurus (Illiger, 1815) or maned wolf as it is popularly known, is the largest canid in South America, has a wide distribution, being found in open environments, shrubs, savannas, swamps, forests along water courses and environments altered by anthropic actions. With the reduction of their natural habitat by human activities such as agriculture, livestock and urbanization, their populations have been decreasing. Thus, one of the ways to contribute to the conservation and persistence of the species, is an analysis of its diet, obtaining important information such as its distribution, identification of individuals and genetic diversity of the population. Thus, the present study analyzed the literature about the maned wolf's diet, seeking to understand the state of the art and identifying qualitative and quantitative patterns in the composition of its diet. We considered academic papers that collected and sorted the fecal material from C. brachyurus and described all the items consumed. We selected 26 studies for analysis, published between the years 1984 and 2019. The results show that the maned wolf's diet studies were more frequent in the Cerrado biome and in the state of Minas Gerais and São Paulo, which can be explained by its wide range distribution in this biome. The period with the largest number of publications about the subject was between 2000 and 2009, with the predominance of one author per publication, publications in the format 'Article' or 'Dissertation' were the most used. There was no difference between the number of feces collected in the dry and rainy seasons. There were 28,582 occurrences of food items, the majority of them were plants (60.49%) and the remaining animals (39.51%), distributed in four Phylums, 14 classes, 63 orders, 111 families, 164 genera and 159 species. Regarding morphospecies, 329 were identified, 192 were from animals e 137 of vegetables . Items of flora such as Solanaceae and Arecaceae were frequent in the maned wolf's diet. Among the animal items, mammals were the group found most frequently, followed by arthropods, birds, reptiles. Amphibians, unidentified vertebrates and fish obtained low frequency in the canine diet. The species has an opportunistic and generalist diet, feeding occasionally from local species, and primarily from few wide range species, with a high variability according to the environment where it occurs.